Compressive strength differences between hybrid composites using post curing light box with LED and dry heating, in vitro - Krisnawaty, Jenny; Natasasmita, Setiawan; Aripin, Dudi (Padjadjaran Journal of Dentistry, 2011)
A hybrid type of composite resins is used as dental restorative materials in a wide cavity directly or indirectly. The mechanical properties of the composite resin would increase post-curing. The purpose of this study was to determine the differences between the compressive strength of hybrid type composite resin post-curing using LED light box and dry heating. This type of research was a quasi-experimental in vitro with the sample size of 30 samples which were divided into two groups. Each sample was tested using a Universal Testing Machine (Lloyd) at a speed of 1 mm/minute to test the compressive strength. Compressive strength values were recorded when the sample broke. The average value of compressive strength of the two treatment groups was statistically calculated using t-test. The results, of this study, showed that a hybrid composite resin with post curing using a light box with LED was at 194.138 Mpa which was lower than using the dry heat of 227.339 Mpa. It showed the statistically significant difference. The conclusion of this study was that the compressive strength of post-cured hybrid composites using a light box with LED was significantly lower than the post-curing using dry heat.